Thoracoscopic McKeown esophagectomy in a patient with an azygos lobe - Rie Nakashima; Kohei Tajima; Kazuo Koyanagi; Akihito Kazuno; Miho Yamamoto; Yoshiaki Shoji; Kentaro Yatabe; Kohei Kanamori; Mika Ogimi; Kazuhito Nabeshima; Kenji Nakamura; Masaki Mori (Journal of Cardiothoracic Surgery, 2024)
Abstract Background The azygos lobe is a relatively rare anatomical variation, and there have been no reports, until date, of thoracoscopic McKeown esophagectomy for esophageal cancer in a patient with an azygos lobe. The azygos lobe can be diagnosed by chest X-ray or CT, and is usually not associated with any symptoms. However, surgeons should be aware that transthoracic surgical procedures in patients with an azygos lobe could be associated with a high risk of complications. Case presentation An 83-years-old man was brought to our emergency room with fever, severe headache, and difficulty in moving. MRI revealed a brain abscess, which was treated by abscess drainage and systemic antibiotic treatment. Further examinations to determine the cause of the brain abscess revealed esophageal cancer. In addition, CT revealed an azygos lobe in the right thoracic cavity. Although intrathoracic adhesions were anticipated on account of a previous history of bacterial pyothorax, we decided to perform esophagectomy via a thoracoscopic approach. Despite the difficulty in dissecting the intrathoracic adhesions, we were able to obtain the surgical field thoracoscopically. Then, we found the azygos lobe, as diagnosed preoperatively, and the azygos vein was supported by the mesentery draining into the superior vena cava. After dividing the mesentery, we clipped and cut the vessel, and both ends were further ligated. After these procedures, we safely performed esophagectomy with 3-field lymph node dissection. The postoperative course was uneventful, and the patient was discharged on the 21st postoperative day. Conclusions Although there was a firm adhesion in the thoracic cavity, preoperative recognition of the azygos lobe could help in preventing intraoperative injury. Especially, esophageal surgeons are required to deal with the azygos lobe safely to avoid serious intraoperative injury.